2021
DOI: 10.1227/ons.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Multiple-Layered Anterior Skull Base Reconstruction Using a 360° Suturing Technique

Abstract: BACKGROUND:Advances in technique and instrumentation have improved outcomes after resection of anterior skull base tumors. However, cerebrospinal fluid (CSF) leak occurs in 4%-20% of patients. To reduce the risk of CSF leak, we have developed a novel reconstruction technique that consists of a 4-layered graft with patchwork suturing and hard material.OBJECTIVE:To evaluate the effectiveness of this reconstruction technique when used for resection of anterior skull base tumors.METHODS:This case series included 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Septoplasty from the unaffected side with an extended anterior Killian incision. A lateral Y‐shaped nasal septal mucosal incision enables tumor mobilization 7,13 . Most previous studies on olfactory neuroblastoma excision have reported tumor resection via a staged or piecemeal approach 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Septoplasty from the unaffected side with an extended anterior Killian incision. A lateral Y‐shaped nasal septal mucosal incision enables tumor mobilization 7,13 . Most previous studies on olfactory neuroblastoma excision have reported tumor resection via a staged or piecemeal approach 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…A lateral Y-shaped nasal septal mucosal incision enables tumor mobilization. 7,13 Most previous studies on olfactory neuroblastoma excision have reported tumor resection via a staged or piecemeal approach. 14,15 Although technically demanding, en bloc resection has several theoretical merits, including a lower possibility of tumor dissemination and accurate pathological examination.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Skull base reconstruction surgery is often associated with complications such as spinal fluid leakage and infection. However, skull base surgery using a 4‐layer reconstruction method was performed in our hospital without postoperative complications, such as spinal fluid leakage, 18 which allowed for quick access to additional postoperative radiation therapy. All patients, except those with a low‐grade Kadish–Hyams classification and complete resection, were treated with additional postoperative radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, autologous fascia lata and VP-NSF provide good watertight properties to prevent CSF leaks. In recent years, based on the multilayer repair technique, surgeons have also made some suture improvements, such as the technique of continuous suturing of the dura with fascia lata grafts, a method of 360° closure by suturing 11 points around the defect, and a nasal septum bone ap combined with VP-NSF [8][9][10]. These factors have further reduced the rate of CSF leaks and related complications.…”
Section: Introductionmentioning
confidence: 99%